Obstetric Outcome in Women with First Trimester Vaginal Bleeding - Shafqat, Maha; Sultana, Nayyer; Khan, Faiza; Malik, Uzma; Khan, Tehreema; Majeed, Tayyaba (Indus Journal of Bioscience Research, 2025)
Background: First-trimester vaginal bleeding is one of the most common complications of early pregnancy, affecting nearly one in four women. Objective: To assess the obstetric and neonatal outcomes in women presenting with first-trimester vaginal bleeding and to evaluate the relationship between bleeding severity and adverse pregnancy outcomes. Methodology: This Cross-sectional study was conducted at the Department of Obstetrics and Gynecology, Central Park hospital from 15th September, 2023 to 15th march, 2024Two hundred pregnant women with first-trimester vaginal bleeding were enrolled using random sampling. Pregnant women aged 20–40 years presenting with vaginal bleeding during the first trimester were included. Demographic data, clinical findings, and severity of bleeding were recorded. Ultrasonography was performed to assess pregnancy viability. Results: The mean age of participants was 27.97 ± 4.06 years, and the mean parity was 1.90 ± 0.65. PIH was the most frequent maternal complication (16.5%), followed by oligohydramnios (9.5%) and placental abruption (9.0%). Preterm deliveries occurred in 20% of cases. Neonatal outcomes were generally favorable, with a mean birth weight of 3.10 ± 1.89 kg and no stillbirths, though 18.5% required NICU admission.  Conclusion: It is concluded that first-trimester vaginal bleeding is an important predictor of adverse obstetric outcomes. Moderate to heavy bleeding is significantly associated with PIH, placental abruption, and preterm delivery.